Unsafe fecal disposal practices in children and the nexus with childhood diarrhea in low- and middle-income countries: a systematic review and meta-analysis. (25th October 2022) - Soboksa, Negasa Eshete; Olkeba, Beekam Kebede; Negassa, Belay; Hareru, Habtamu Endashaw; Gudeta, Dinkinesh Begna
Abstract: In household environments, the improper handling of children's feces can be a significant contaminant, raising a high risk of child exposure. Thus, the objective of this study was to pool the available evidence on the prevalence of safe child feces disposal practices and their association with reported childhood diarrhea in low-income and middle-income countries. PubMed, Science Direct, Cochrane Library databases, Ovid Medline, Google Scholar, and references of other studies were searched. The search was limited to studies published in English-language literature. Two independent reviewers used an appropriate tool to critically appraise the selected studies. Stata version 16 was used for the analysis. The pooled prevalence of unsafe disposal of children's feces among 20 studies was 52.63% (95% CI: 0.43–0.62). Overall, the meta-analysis found that unsafe disposal practices insignificantly increased the risk of diarrhea by 4% (OR: 1.04, 95% CI: 0.84–1.24). In the subgroup analysis, unsafe disposal of children's feces decreased the risk of diarrhea in Oceania (OR = 0.75, 95% CI = 0.62–0.88) and increased in Asia (OR = 1.33, 95% CI = 1.25–1.41). In conclusion, the prevalence of unsafe child feces disposal practices was high. There was no significant association between unsafe child feces disposal practices and diarrhea. HIGHLIGHTS: This study aimed to pool the extent of disposal of children's feces and its association with diarrhea in children. This systematic review and meta-analysis included 19 published articles and 1 unpublished study. The pooled prevalence of unsafe maternal/guardian disposal practices for child feces in this study was high. Unsafe disposal practices for children's feces insignificantly increased the likelihood of diarrhea in children.